Solid-state radiation detectors technology and applications - Awadalla, Salah; Iniewski, Krzysztof (CRC Press/Taylor & Francis, 2015)
Solid-State Radiation Detectors: Technology and Applications provides a valuable reference for engineers and scientists looking to enhance the performance of radiation detector technology for medical imaging and other applications.